PENGAWASAN KANTOR OTORITAS WILAYAH VIII PADA STANDAR PELAYANAN PENUMPANG KELAS EKONOMI NIAGA BERJADWAL DALAM NEGERI DI BANDAR UDARA SAM RATULANGI - TAMBINGON, ANITA DEBORA; TAMPI, JOHNNY REVO; LONDA, VERY (Sam Ratulangi University, 2019)
This research was conducted to explain the supervision on the operational standards of domesticscheduled commercial economy class passenger service procedures by the Territory VIII AirportAuthority Office. By using a qualitative design with descriptive analysis, it was found thatsupervision was carried out using Standard Operating Procedure Inspection Procedures forScheduled Commerce Route Permits and Passenger Service Classes of Domestic ScheduledCommercial Air Transport Business Services that were adjusted to the Pre-Flight, In-Flight andPost-Flight stages. The conclusion of the research is that the supervision of Region VIII AirportAuthority Office on the economy class passenger service standard for commercial airtransportation at Sam Ratulangi Airport is done more directly than indirectly. This studyrecommends a regulation that gives authority to the head of the airport authority office to takeaction on the negligence of services, the need for the use of digital corporate government in receivingand following up on errors in the application of standard operating procedures for services, theneed for coordination and synchronization of supervision programs from the Regional AirportAuthority Office VIII with Angkasa Pura II as the manager of Sam Ratulangi Airport and theAirlines operating at Sam Ratulangi Airport.Keywords: Supervision; Standard Operating Procedures; Service